2002
DOI: 10.1002/mc.10061
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator–activated receptor α in the human breast cancer cell lines MCF‐7 and MDA‐MB‐231

Abstract: Peroxisome proliferator-activated receptor (PPAR) alpha is a ligand-activated transcription factor that has been linked with rodent hepatocarcinogenesis. It has been suggested that PPARalpha mRNA expression levels are an important determinant of rodent hepatic tumorigenicity. Previous work in rat mammary gland epithelial cells showed significantly increased PPARalpha mRNA expression in carcinomas, suggesting the possible role of this isoform in rodent mammary gland carcinogenesis. In this study we sought to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 37 publications
3
115
1
Order By: Relevance
“…[6][7][8][9][10][11] These data are in agreement with a recent report that PPARa agonists exert pro-inflammatory activities, and with previous findings stating that certain PPARa agonists promote breast cancer cells proliferation. 28,29 PPARa also regulates the expression of lipoprotein receptors and cholesterol transporters, as apolipoprotein E (ApoE), that contains a PPRE sequence on its promoter. 39 Intriguingly, ApoE over-expression has been documented in normal MS 33 and in prostate CSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11] These data are in agreement with a recent report that PPARa agonists exert pro-inflammatory activities, and with previous findings stating that certain PPARa agonists promote breast cancer cells proliferation. 28,29 PPARa also regulates the expression of lipoprotein receptors and cholesterol transporters, as apolipoprotein E (ApoE), that contains a PPRE sequence on its promoter. 39 Intriguingly, ApoE over-expression has been documented in normal MS 33 and in prostate CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…26 Intriguingly, PPARa, which is activated by the chemical agonist Wy14643 (WY), induces both pro-inflammatory and anti-inflammatory response in target cells. [27][28][29] Here, MS from normal and tumor breast tissues, as well as from tumorigenic MCF7 and non-tumorigenic MCF10 human breast cell lines, were exposed to RARs, RXRs and PPARs agonists. Our data point out that NRs agonists (IIF, RA and PGZ) impair MS formation.…”
Section: Introductionmentioning
confidence: 99%
“…For all experiments mRNA levels were normalized to 18S rRNA and analyzed relative to the appropriate control (as described in the figure legends). Relative expression levels were calculated using the DDCt method (17).…”
Section: Rna Isolation and Real-time Pcrmentioning
confidence: 99%
“…In contrast, PPAR␥ and PPAR␦ agonists have been extensively studied to evaluate their anticancer effects because of their antiproliferative, proapoptotic, antiapoptotic, and differentiation-promoting activity (4). However, recent studies have revealed the expression of PPAR␣ in tumor cells (5,6), and PPAR␣ ligands suppress the growth of several cancer lines, including colon, breast, endometrial and skin, in vitro (7)(8)(9)(10). PPAR␣ ligands also suppress the metastatic potential of melanoma cells in vitro and in vivo (11,12).…”
mentioning
confidence: 99%